2020
DOI: 10.3390/s20174969
|View full text |Cite
|
Sign up to set email alerts
|

In-Service Detection and Quantification of Railway Wheel Flat by the Reflective Optical Position Sensor

Abstract: Railway wheel tread flat is one of the main faults of railway wheels, which brings great harm to the safety of vehicle operation. In order to detect wheel flats dynamically and quantitatively when trains are running at high speed, a new wheel flat detection system based on the self-developed reflective optical position sensor is demonstrated in this paper. In this system, two sensors were mounted along each rail to measure the wheel-rail impact force of the entire circumference by detecting the displacement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Some studies were focused on freight rail transport only (the presented solutions are connected to cars; nevertheless, energy harnessing may also be applied for sensors analyzing tracks; therefore, it is also included in this review paper). The authors of Gao et al [ 142 ] noted that electrical wires are not provided for freight wagons; therefore, power monitoring sensors such as pressure sensors and accelerometers cannot be directly applied for such vehicles’ condition monitoring. Nevertheless, these types of sensors are essential for ensuring operational safety; therefore, the authors investigated the approach of harnessing freight wagons’ vibrational energy in order to power monitoring sensors (a pressure sensor and a triaxial MEMS accelerometer) with the use of an electromagnetic vibrational energy harvester with an inertial pendulum.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies were focused on freight rail transport only (the presented solutions are connected to cars; nevertheless, energy harnessing may also be applied for sensors analyzing tracks; therefore, it is also included in this review paper). The authors of Gao et al [ 142 ] noted that electrical wires are not provided for freight wagons; therefore, power monitoring sensors such as pressure sensors and accelerometers cannot be directly applied for such vehicles’ condition monitoring. Nevertheless, these types of sensors are essential for ensuring operational safety; therefore, the authors investigated the approach of harnessing freight wagons’ vibrational energy in order to power monitoring sensors (a pressure sensor and a triaxial MEMS accelerometer) with the use of an electromagnetic vibrational energy harvester with an inertial pendulum.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…These systems in Gao et al [ 142 , 144 , 145 ] are called self-powered wireless sensor networks for wireless communication . The condition-monitoring system based on energy harvesting was described in the abovementioned paper Gao et al [ 142 ].…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For detecting and quantifying online dynamic wheel flats when trains reached high speed, Gao et al [33] demonstrated…”
Section: Fiber Bragg Gratingmentioning
confidence: 99%
“…In this work, a wayside monitoring strategy is adopted for wheel flat detection using sensors with the emphasis on their optimal position of installation. Similar work for detecting wheel flats is proposed using a reflective optical position sensor where not only the position of the wheel flat is determined but also its quantification is realized [31]. However, quantification of wheel flats is still a daunting challenge for the research community due to the limitations of the various measuring conditions.…”
Section: Conicity Managementmentioning
confidence: 99%